Pengaruh Bauran Komunikasi Pemasaran Terhadap Proses Keputusan Pembelian Konsumen Provider Tri di Kota Denpasar - Novita Devi, Ida Ayu Chandra Surya; Giantari, I Gusti Ayu Ketut (E-Jurnal Manajemen, 2014)
This research aims to determine the effect of the marketing communications mix to consumer buying decision process tri provider in the city of Denpasar. Analysis of the data used is a descriptive analysis, multiple linear regression analysis with factor analysis. The results analysis coefficient of determination (R 2 ) unknown amount of 0.648. It shows that 64,8% of variation changes the variable rise and fallvariables change consumer buying decision process is influenced by the marketing communication mix variables, while the remaining 39,2% is influenced by other variables not included in the model. The results of this study showed a significant effect simultaneously and partially between the marketing communications mix to consumer buying decision process Tri provider in the city of Denpasar.. Normal 0 false false false EN-US X-NONE X-NONE
Keywords: Marketing Communications, Consumer Buying Descision Process